Removal Techniques of Nitrate from Water: A Review - Mohsenipour1, Morteza; Shahid1, Shamsuddin; Ebrahimi2, Kumars (Asian Journal of Chemistry, 2014)
Nitrate pollution of water is a major environmental problem all over the world. Consequently, numerous techniques have been developed to remove or reduction of nitrate in water. A review of removal techniques of nitrate from water has been carried out in this paper. Recent literatures related to various techniques including reverse osmosis, ion exchange, electrodialysis, biological denitrification, chemical denitrification, adsorption methods using different adsorbents like carbon base, agricultural waste, natural materials are systematically review to assess their performance. The paper reveals that adsorption could be the most promising technique of removal of nitrate from water in near future.